A Meta-Analysis of Glasgow Prognostic Score and Modified Glasgow Prognostic Score as Biomarkers for Predicting Survival Outcome in Renal Cell Carcinoma - Tong, Tongyu; Guan, Yupeng; Xiong, Haiyun; Wang, Liling; Pang, Jun (Frontiers in Oncology, 2020)
Purpose Accumulative studies suggest the Glasgow prognostic score (GPS) and modified Glasgow prognostic score (mGPS) to be potential biomarkers; however, their prognostic value remains debatable. Our meta-analysis focused on assessing the accurate prognostic value of GPS and mGPS in patients with renal cell carcinoma (RCC) in addition on their effectiveness. Methods To investigate the relationship between mGPS/GPS and prognostic value in patients with RCC, we performed a comprehensive retrieval for relevant articles from databases such as PubMed, Embase, Web of Science and Medline up to 1st Feb, 2020. STATA 15.0 software was used to obtain pooled hazard ratios (HRs) and their 95% confidence intervals (CIs) for survival outcome, including overall survival (OS), recurrence-free survival (RFS)，progression-free survival (PFS) and cancer-specific survival (CSS). A formal meta-analysis of these outcomes was performed. Results In total, 2,691 patients with RCC were enrolled from 15 cohort studies. Higher GPS/mGPS (GPS/mGPS of 2) indicated poorer OS, CSS, PFS and RFS in patients with RCC. Similarly, medium GPS/mGPS (GPS/mGPS of 1) also had a significant association with poorer OS, CSS, PFS and RFS but superior than higher GPS/mGPS in these patients. Conclusion GPS and mGPS are effective biomarkers for predicting prognosis in patients with RCC, and higher GPS and mGPS are closely related to inferior survival outcomes. More randomised controlled trials are needed to investigate the promising value of GPS/mGPS in the future.